2016
DOI: 10.32385/rpmgf.v33i3.12159
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização da empatia em internos de medicina geral e familiar

Abstract: The aim of this study was to assess empathy in family medicine trainees and to compare the level of empathy in first and final year trainees. Type of study: Cross-sectional. Location: Healthcare Regional Administrations (HRA) in Portugal. Population: Family medicine trainees in Portuguese HRA. Methods: We gave an anonymous, self-administered questionnaire, including the Jefferson Scale of Physician Empathy (JSPE), adapted and validated for Portugal, to a convenience sample of family medicine residents. The sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
1
1
3
Order By: Relevance
“…There There was no statistical difference between the total empathy score between men and women. This finding contradicts the results of many international studies on empathy in medical students, which found higher scores in women 6,10,[18][19][20][21][22][23] . one showed a higher empathy score in women 27 and the other observed similar values between women and men 3 .…”
Section: Resultscontrasting
confidence: 98%
“…There There was no statistical difference between the total empathy score between men and women. This finding contradicts the results of many international studies on empathy in medical students, which found higher scores in women 6,10,[18][19][20][21][22][23] . one showed a higher empathy score in women 27 and the other observed similar values between women and men 3 .…”
Section: Resultscontrasting
confidence: 98%
“…Segundo o estudo de Paro (2013), realizado com 1350 alunos, através da Escala Multidimensional de Reatividade Interpessoal de Davis -EMRI, a comparação dos escores de empatia entre homens e mulheres revelou diferenças significativas entre os sexos, sendo maiores entre as mulheres. Resultados semelhantes foram encontrados por Provenzano et al (2014), por Basílio et al (2017), assim como por Nascimento et al (2018), que utilizaram a Escala de Jefferson. Ulloque et al (2019) reafirmou menores níveis empáticos entre estudantes de medicina do sexo masculino, assim como no estudo de Chatterjee et al (2017) e no de Esquerda et al (2016).…”
Section: Empatia Em Estudantes De Medicina E Fatores Associadosunclassified
“…A empatia revela-se importante ferramenta utilizada na construção da relação entre o médico e o doente, interferindo positivamente na qualidade dos cuidados prestados e com melhora na acuidade diagnóstica e adesão terapêutica (Basílio et al, 2017). Nesse sentido, a relevância da boa comunicação na relação médico-paciente tem sido demonstrada de forma recorrente.…”
Section: Relação Entre Empatia E a Prática Médicaunclassified
See 1 more Smart Citation
“…These components of empathy are dissociable, as they use different neural networks 7 . Empathy is related to the emotional response arising from the apprehension or understanding of the emotional state of the other, being an important factor for establishing interpersonal relationships and, therefore, particularly relevant in the doctor-patient relationship 8,9 . Studies have suggested that medical students' empathy may change throughout the course, ranging from a small increase to a decrease in it 10,11,12 .…”
Section: Introductionmentioning
confidence: 99%